2022
DOI: 10.2217/fmb-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches to Combat the Global Antibiotic Resistance Challenge

Abstract: Antimicrobial resistance (AMR) has become a major concern for healthcare workers due to the emergence of new variants of resistant markers, especially carbapenemases. Combinational antibiotic therapy is one of the best and easiest approaches to handle the current situation of AMR. Although some antibiotic combinations are already in clinical use, they remain to be studied in detail. This review focuses on therapeutic options for AMR mechanisms of resistance in bacteria that can be overcome by combinational the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The emergence of beta-lactamases such as bla NDM , extended spectrum beta lactamases (ESBLs) such as bla CTX-M , bla SHV , and bla TEM etc. has led to the use of last resort antibiotics such as tigecycline, polymyxin E, daptomycin, vancomycin and linezolid [ 84 – 86 ]. However, in the last decade several ARGs against the last-line antibiotics have been reported [ 87 – 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of beta-lactamases such as bla NDM , extended spectrum beta lactamases (ESBLs) such as bla CTX-M , bla SHV , and bla TEM etc. has led to the use of last resort antibiotics such as tigecycline, polymyxin E, daptomycin, vancomycin and linezolid [ 84 – 86 ]. However, in the last decade several ARGs against the last-line antibiotics have been reported [ 87 – 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences have showed that antibiotic combination therapy provides an effective solution to antibiotic resistance (Coates et al., 2020 ; Farhat and Khan, 2022 ; Scudeller et al., 2021 ). However, how these antibiotics work together and how their underlying mechanisms operate are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol is monoterpenoid phenol that has profound antibacterial activity and it alters the membrane permeability so, combination therapy using Topoisomerase inhibitors and plant-based nanoparticles may be an alternate treatment for resistant bacteria ( Marinelli et al, 2018 ). Combination therapy is a strategy that combines two or more therapeutic drugs to achieve synergism, dose reduction and protection from bacterial resistance ( Farhat and Khan 2022 ).…”
Section: Discussionmentioning
confidence: 99%